STUDENTS’ ANXIETY IN LEARNING ENGLISH AT THE TENTH GRADE TKJ STUDENTS OF SMK NEGERI 2 SIDUAORI - Halawa, Asalia; Laia, Restu Damai; Zagoto, Impiani; Wau, Senadaman (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2024)
This research was carried out to investigate the students’ anxiety in learning English at the tenth grade TKJ of SMK Negeri 2 Siduaori. The objectives of this research were to find out the types of students’ anxiety in learning English at the tenth grade TKJ of SMK Negeri 2 Siduaori and to explain the factors contributing to the students’ anxiety in leraning English to tenth grade TKJ of SMK Negeri 2 Siduaori. This research was a qualitative research design and the data were obtained through the classroom observation and interviews. The data were analyzed by using Miles and Huberman’ theory such as data reduction, data display and conclusion drawing and verification. The result of this study showed that the students at the tenth grade TKJ of SMK Negeri 2 Siduaori were experienced the anxiety in learning English. There were two types of anxiety experienced by the students such as state anxiety and trait anxiety. The factors that contribute to the students’ anxiety in learning English such as speaking in front of the class, being called by the teacher, incomprehensible input or unclear explanation, being ridiculed by peers/classmates, inappropriate teaching method, low self-esteem, lack of preparation, students’ beliefs about learning English, English is excessive, and stressful learning experience. The researcher figured out that the sources of these factors do not only come from the teacher but also from the students. Thus, it is extremely important to increase teacher’s awareness since anxiety is the main factor which affects the students’ learning. Knowing the students’ anxiety in learning will absolutely influence the teacher in treating the students properly. The students should respect each others and support each others in growing together and developing skills in the class.